Pengaruh Promosi, Online Customer Review, dan Online Customer Rating Terhadap Keputusan Pembelian (Studi Pada Pengguna Marketplace Shopee Di Indonesia - W. Heni Puspita Sari (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2021)
AbstractThis study aims to determine the effect of promotions, online customer reviews, and online customer ratings on purchasing decisions for Shopee marketplace users in Indonesia. This type of research is explanatory research with a quantitative approach. The population used is Shopee marketplace users in Indonesia. The data was obtained from a questionnaire that was filled out online, the sample was drawn using probability sampling with a purposive sampling technique with a sample of 100 respondents. Data analysis used descriptive statistical analysis and classical assumption test with SPSS 28.0 application tools. Based on the results of the t-test (partial) shows that the variables of promotion, online customer review, and online customer rating each have a significant effect on purchasing decisions. The results of the F (simultaneous) test explain that promotion, online customer review, and online customer rating together have a significant effect on purchasing decisions. Then the R2 test shows that as many as 57.9% of purchasing decisions are influenced by promotions, online customer reviews, and online customer ratings and the remaining 42.1% of purchasing decisions are influenced by other variables. Keywords: Promotion, Online Cutomer Review, Online Customer Rating, Purchase Decision.